Carp (Cyprinus carpio) lipovitellin is a highly stable phospholipoglycoprotein with the same immunogenicity as vitellogenin. (14th January 2018) - Wang, Jun; Zhang, Zhenzhong; Wei, Yanyan; Zheng, Mingyi; Ru, Shaoguo
Abstract: Vitellogenin (Vtg) induction in carp ( Cyprinus carpio ) is a commonly used biomarker for oestrogenic contamination. However, the accurate quantification of Vtg was challenged because the easy degradation of Vtg standard would change the standard curves of the immunoassays. In this study, three yolk proteins were purified from carp ovarian extracts by a two‐step chromatographic method. The purified proteins were characterized as phospholipoglycoproteins with molecular weights of approximately 416, 398 and 383 kDa. In SDS‐PAGE, the purified proteins appeared as a major band of approximately 110 kDa and several faint bands. Based on these characteristics, purified proteins were identified as carp lipovitellin (Lv). Immunological analysis showed that anti‐Vtg antiserum reacted with the purified Lv. The results of stability analysis revealed that even heated at 60°C for 60 min, the electrophoretic patterns of carp Lv in native‐PAGE and SDS‐PAGE did not have a significant difference compared with the Lv solution stored at 4°C. Therefore, the purified carp Lv was confirmed to have similar immunogenicity with Vtg and possess exceptionally high stability, which would be helpful for the development of robust immunoassays for accurate quantification of carp Vtg.